Poly-Lipoic Ester-Based Coacervates for the Efficient Removal of Organic Pollutants from Water and Increased Point-of-Use Versatility - Zhang, Zhao; Liu, Qian; Sun, Zhimin; Phillips, Bailey K; Wang, Zhenzhen; Al-Hashimi, Mohammed; Fang, Lei; Olson, Mark A (Chemistry of materials, 2019)
The increasing frequency with which organic pollutants can be found in global surface water poses a formidable threat to both our environment and its creatures. While the problem has attracted adequate attention, current water treatment tools such as commercially available active carbon still cannot satisfy the remediating necessity due to its unfavorable rate of uptake and high regenerating cost. Moreover, water-insoluble pollutant adsorbents typically suffer from poor processability, effectively decreasing their potential for increased point-of-use versatility. Herein, we report a solution processable poly-lipoic ester-based material that readily undergoes simple coacervation upon ultrasonic solution processing. This material exhibits excellent removal efficiencies (>90%) and material recyclability for the uptake of highly concentrated typical pollutants including a plastic component bisphenol A (BPA), a pharmaceutical residue valsartan, and an industrial dye fluorescein from water. The polymer is conveniently accessible by a solvent-free, thermally initiated disulfide exchange ring-opening polymerization of a lipoic ester derivative and is postfunctionalized with an amphiphilic, π-electron-deficient bipyridinium-based side chain. Solution processing of this material facilitated the development of a pollutant sponge, which operates via a dip-remove-squeeze action, with an adsorption rate constant for BPA ∼85 times greater than its progenitor and achieving 80% removal efficiency in 30 s. This approach is particularly promising for quick point-of-use treatment of wastewater with high chemical oxygen demand. These results highlight the importance for material processability in the development of water-insoluble molecular adsorbents and establish poly-lipoic ester-based materials as contending precursors for application-driven soft matter development.